1988
DOI: 10.1097/00004032-198802000-00004
|View full text |Cite
|
Sign up to set email alerts
|

Transfer Coefficients of Selected Radionuclides to Animal Products. I. Comparison of Milk and Meat From Dairy Cows and Goats

Abstract: The diet-milk transfer coefficient, Fm (Bq L-1 output in milk divided by Bq d-1 intake to the animal) was studied for eight radionuclides that previously had been given little attention. The Fm values for cows and goats, respectively, were: 2.3 X 10(-5) and 1.5 X 10(-4) for 99mTc, 1.4 X 10(-4) and 8.5 X 10(-4) for 95mTc, 1.1 X 10(-2) for 99Tc (goats only); 1.7 X 10(-3) and 9 X 10(-3) for 99Mo; 4.8 X 10(-4) and 4.4 X 10(-3) for 123mTe; 4.8 X 10(-4) and 4.6 X 10(-3) for 133Ba; 5.5 X 10(-7) and 5.5 X 10(-6) for 9… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
20
0

Year Published

1991
1991
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 0 publications
3
20
0
Order By: Relevance
“…However, this value is based on a single stable milk concentration and four unassociated plant concentrations, assuming 10 kg d À1 (DW) intake. The only other data available gives an F m value of 5.5 Â 10 À7 d L À1 based on single administration of 95 Zr oxalate to one cow (Johnson et al, 1988). The Russian data, based on many more experimental animals than has previously been available, suggest that a higher value might be more appropriate than that currently used in TRS 364 (IAEA, 1994) which is based on the data of Johnson et al (1988).…”
Section: Zrmentioning
confidence: 98%
“…However, this value is based on a single stable milk concentration and four unassociated plant concentrations, assuming 10 kg d À1 (DW) intake. The only other data available gives an F m value of 5.5 Â 10 À7 d L À1 based on single administration of 95 Zr oxalate to one cow (Johnson et al, 1988). The Russian data, based on many more experimental animals than has previously been available, suggest that a higher value might be more appropriate than that currently used in TRS 364 (IAEA, 1994) which is based on the data of Johnson et al (1988).…”
Section: Zrmentioning
confidence: 98%
“…Also, the Fm data for Zn from this study was an order of magnitude higher than that from other studies possibly because (i) Zn can be combined with other metals to form alloys, mainly of nickel, that are used to make stainless steel milk vats and (ii) Zn present in galvanized metal is often present in barns and may be licked by animals. The Fm value for Ba was also two orders of magnitude higher than other two reported Fm values for this element retained in the dataset (Johnson et al 1988 andJohnson 1983).…”
Section: The Goat Milk Dataset Revisionmentioning
confidence: 58%
“…Review source information Coughtrey (1990 Bishop et al (1989)  References supplying data for more than three elements in animal products Ennis et al (1988…”
Section: Meat Milk Meat Milk Meat Milk Meat Eggs Meatmentioning
confidence: 99%
See 1 more Smart Citation
“…However, Ng et al (1982), the originators of the values quoted in IAEA (1994), note that their suggested transfer coefficient appears high but were unable to explain why on the basis of the limited data they had available. Johnson et al (1988) report a value of 6 Â 10 À5 d kg À1 for the transfer coefficient of 95 Nb to goat meat when administered as 95 Nb (III) oxalate; IAEA (1994) recommend a value of 3 Â 10 À4 d kg À1 for sheep meat. The results reported here suggest that the transfer to liver and kidney may be at least two to three orders of magnitude higher than that for meat.…”
Section: Radionuclide Transfer Parametersmentioning
confidence: 99%